(untitled) (MAUSAM, 1980)
Variations in runway temperature affect air density over the runway and this affects the lift of an aircraft and its effective payload. Temperature measured by an electrical thermometer installed near the runway (indicated as R) has been found to vary with temperature measured by a thermometer placed in a Stevenson’s screen (indicated as S) within a wide limit of +5. 9 deg. C to -4.0 deg. C. This study is based on observations at Santacruz airport and discusses the diurnal, seasonal and annual variations of (R-S). Causes of such variations have also been investigated.